2016
DOI: 10.1681/asn.2014121181
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Lkb1 in Renal Tubular Epithelial Cells Leads to CKD by Altering Metabolism

Abstract: Renal tubule epithelial cells are high-energy demanding polarized epithelial cells. Liver kinase B1 (LKB1) is a key regulator of polarity, proliferation, and cell metabolism in epithelial cells, but the function of LKB1 in the kidney is unclear. Our unbiased gene expression studies of human control and CKD kidney samples identified lower expression of LKB1 and regulatory proteins in CKD. Mice with distal tubule epithelial-specific Lkb1 deletion (Ksp-Cre/Lkb1 flox/flox ) exhibited progressive kidney disease cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 62 publications
5
81
0
Order By: Relevance
“…An inability to switch metabolism from aerobic glycolysis to OXPHOS, and thus ‘turn off’ inflammation, has been associated with chronic inflammation and impaired organ recovery 62 . In inflammatory cells, the switch from this early anabolic glycolytic phase to an adaptive catabolic phase in which metabolism is reprogrammed towards OXPHOS and regulated to conserve energy, has been attributed to the action of Sirt1 and Sirt6 (REF.…”
Section: The Key Role Of Metabolic Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…An inability to switch metabolism from aerobic glycolysis to OXPHOS, and thus ‘turn off’ inflammation, has been associated with chronic inflammation and impaired organ recovery 62 . In inflammatory cells, the switch from this early anabolic glycolytic phase to an adaptive catabolic phase in which metabolism is reprogrammed towards OXPHOS and regulated to conserve energy, has been attributed to the action of Sirt1 and Sirt6 (REF.…”
Section: The Key Role Of Metabolic Regulationmentioning
confidence: 99%
“…3). Mice that were deficient in upstream regulators of NAD + /NADPH or were exposed to FAO inhibitors had substantial energy deficiencies, increased apoptosis and profibrotic phenotypes, all of which could be reversed by treatment with upstream activators of PGC-1α such as fenofibrate 62 .…”
Section: The Key Role Of Metabolic Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations only support the potential benefit of improving bioenergetics, but not directly PGC1α. There are several other transcription factors in the kidney those expression is also reduced in glomerulosclerosis and might have overlapping functions with PGC1α (30)(31)(32)(33)(34). For this reason, here we performed studies to directly address the role of PGC1α in podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This newly observed evidence strongly suggests the correlation between cell polarity and CKD. 10 Besides the above-mentioned pathological observations, large-scale retrospective studies suggested a high-level plasma copeptin (a surrogate of vasopressin), is associated with the progression of kidney diseases. [11][12][13][14][15] For example, positive associations were found between copeptin levels with disease severity in autosomal dominant polycystic kidney disease (ADPKD) patients.…”
Section: Introductionmentioning
confidence: 99%